Relationship between alkaline phosphatase and impaired coronary flow in patients with ST-segment elevated myocardial infarction. Issue 9 (September 2018) - Edem, Efe
Objective: Recent studies have shown that alkaline phosphatase (ALP) might play a negative role in clinical outcomes of patients with peripheral and coronary artery disease. This study aimed to investigate the relationship between serum ALP levels and coronary thrombolysis in myocardial infarction (TIMI) frame counts in patients with ST-segment elevated myocardial infarction undergoing primary percutaneous coronary intervention (PCI). Methods: A total of 198 patients were enrolled in the current study. Serum ALP levels were measured in lithium-heparin plasma samples via a standardized, colorimetric enzyme assay. Coronary TIMI flow was evaluated by counting the number of cine frames that were required for contrast to reach a standardized distal coronary landmark in the culprit vessel. Results: The Spearman correlation coefficient test showed strong positive relationships between coronary TIMI frame counts after primary PCI and serum ALP levels on admittance for the left anterior descending, circumflex, and right coronary arteries (r = 0.774, r = 0.831, and r = 0.730, respectively). Conclusion: Elevated serum ALP levels appear to be a predictor of impaired coronary TIMI frame count in patients suffering from ST-segment elevated myocardial infarction.